La cultura organizacional y su influencia en el desempeño laboral de los empleados del Gobierno Autónomo Descentralizado Municipal del cantón Macará, año 2023. - Ramírez Ato, Neydi Johana (2024)
The objective of this research work was to analyze the organizational culture and its influence on the work performance of the employees of the Municipal Decentralized Autonomous Government of the Macará Canton, period 2023. Therefore, we proceeded to identify the factors of organizational culture in the employees of the Municipal Decentralized Autonomous Government of the Macará Canton; to determine the incidence of organizational culture on work performance; and to establish strategies to improve and strengthen an adequate organizational culture in the GAD. The research was developed from a mixed, non- experimental approach and the following methods were used: descriptive, deductive, synthetic and statistical. The technique used was direct observation by means of an observation form, which was previously elaborated based on the proposed objectives. In addition, the survey was applied to all public servants of the GAD, and the interview was applied to the head of human talent and the financial director in order to obtain relevant information on the research topic. The main conclusion is that the factors of organizational culture are fulfilled in a considerable way, and that organizational culture and work performance have a considerable positive relationship of 0.512* according to Spearman's Rho test, which finally served to establish strategies to improve and strengthen an adequate organizational culture within the Municipal Government.